The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.3341/kjo.2005.19.4.281
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry Analysis of the Retinal Nerve Fiber Layer Thickness in Normal Eyes using Optical Coherence Tomography

Abstract: In normal subjects without significant anisometropia, there was significant asymmetry of the RNFLT for each eye as well as between the right and left eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
24
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 16 publications
3
24
2
Order By: Relevance
“…In our study, the mean difference in all quadrants was 4.23 µm. This observation is consistent with the results of other authors, but the difference was smaller and ranged from 0.52 µm to 3.27 µm [8][9][10]. The only difference in ONH parameters was the larger RV in the right eyes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our study, the mean difference in all quadrants was 4.23 µm. This observation is consistent with the results of other authors, but the difference was smaller and ranged from 0.52 µm to 3.27 µm [8][9][10]. The only difference in ONH parameters was the larger RV in the right eyes.…”
Section: Discussionsupporting
confidence: 83%
“…The introduction of optical coherence tomography (OCT) into clinical practice has allowed direct measurement of the RNFL thickness. To date, studies that implemented both time domain OCT (TdOCT) and spectral domain OCT (SdOCT) have focused either on circumpapillary RNFL (cpRNFL) analysis or measurement of RNFL thickness in the macular area [8][9][10][11]. These studies have demonstrated a significant increase in the asymmetry of the cpRNFL and total retinal thicknesses at the macula in patients with POAG when compared with a normal population [12][13].…”
mentioning
confidence: 99%
“…[41][42][43][44][45][46]53,54 This study focuses on asymmetry analysis using the second method and demonstrates that OAG eyes exhibit significantly greater intereye mean RNFL asymmetry compared with normal eyes (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…RNFL thickness asymmetry can be an early sign of glaucomatous damage and has been explored by OCT technology using 2 main methods: (1) assessing RNFL thickness asymmetry between vertically opposing quadrants of the same eye 41,46,[50][51][52][53] ; and (2) assessing intereye RNFL asymmetry for global average and for quadrants and sectors. [41][42][43][44][45][46]53,54 This study focuses on asymmetry analysis using the second method and demonstrates that OAG eyes exhibit significantly greater intereye mean RNFL asymmetry compared with normal eyes (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation